A Refined Astrometric Approach Based on the Precision Premium and its Application to the Jupiter’s Satellite Himalia - Z. J. Zheng; Q. Y. Peng; F. R. Lin; D. Li (The Astronomical Journal)
Since the advent of Gaia catalog, positional precision of a ground-based telescope can be greatly improved by correction of more subtle errors, including positional biases induced by atmospheric turbulence, and some instrumental factors such as geometric distortion and the charge transfer efficiency. In our previous work, the correlation of positional precision as a function of two objects’ separation is studied and found to be effectively modeled by a sigmoidal function, which provides a good description of this rule. Based on our understanding of the physics of the precision premium, we further refine the astrometric approach in this paper, which determines a target's position in a small region through a weighting scheme. Based on the reductions of the observations of several open clusters and Himalia, Jupiter's largest irregular satellite, the refined approach has demonstrated substantial improvements in positional precision, particularly in scenarios where a sufficient number of reference stars are present in dense fields. We suspect that the contributing factor might be the refined approach's ability to mitigate not only turbulence effects but instrumental effects as well, prevalent among closely spaced star images, given that the approach focuses on localized measurements within a confined area.